Evaluating the Neuroprotective and Antioxidant Effects of Orgaheal™ Ashwagandha with Valerian Root caplet in Oxidative Stress Models: In vitro study - Rajendran; Raj, Sudesh; Tejas; Jayakumar; Sneha; Reethi (International Journal of Pharmaceutical Investigation, 2025)
Background Ashwagandha (Withania somnifera), traditionally valued for enhancing stress resilience, is known for its neuroprotective and antioxidant effects. This study explores the Orgaheal™ Ashwagandha with Valerian Root, which includes Ashwagandha Root Powder, Ashwagandha Root Extract, and Organic Valerian Extract, for potential use in stress management and sleep enhancement. Materials and Methods This study investigated the antioxidant, neuroprotective, and adaptogenic effects in aqueous extract of Ashwagandha Formula (AAE) using in vitro assays. Antioxidant activity was assessed via DPPH, FRAP, and other radical scavenging assays. Neuroprotective effects were evaluated in SH-SY5Y neuroblastoma cells exposed to Dex-induced oxidative stress, measuring cell viability, ROS, apoptosis, and protein expressions (BDNF, pTrkB, CREB). Results and Discussion AAE demonstrated significant antioxidant activity, BChE inhibition (IC50: 4.8 mg/mL), and neuroprotective effects, likely due to withanolides and valerenic acid. These compounds reduced ROS, apoptosis, and restored antioxidant levels. In SH-SY5Y cells under Dex-induced oxidative stress, AAE improved cell viability and morphology, reversing Dex-induced suppression of BDNF, pTrkB, and CREB (all p<0.001), thereby enhancing cellular resilience. Conclusion Orgaheal™ Ashwagandha with Valerian Root, rich in withanolides and valerenic acid, offers potent antioxidant and neuroprotective effects, helping mitigate stress and enhance mental resilience.
Keywords: Antioxidant activity; Neuroprotection; Orgaheal™ Ashwagandha with Valerian Root; Oxidative stress; Valerenic Acid; Withanolides